The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1371/journal.pone.0085120
|View full text |Cite
|
Sign up to set email alerts
|

Glaucocalyxin A Inhibits Platelet Activation and Thrombus Formation Preferentially via GPVI Signaling Pathway

Abstract: Platelets play a pivotal role in atherothrombosis and the antiplatelet agents have been proved to be useful in preventing onset of acute clinical events including myocardial infarction and stroke. Increasing number of natural compounds has been identified to be potential antiplatelet agents. Here we report the antiplatelet effect of glaucocalyxin A (GLA), an ent-diterpenoid that we isolated and purified from the aerial parts of Rabdosia japonica (Burm. f.) var. glaucocalyx (Maxim.) Hara, and investigate the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…GLA inhibited platelet aggregation induced by collagen-related peptide (CRP), a GPVI specific agonist in a dose-dependent manner and reduced collagen-induced phosphorylation of three major molecules, tyrosine kinase Syk, LAT, and phospholipase C γ 2 in GPVI signaling pathway. Therefore, GLA can be developed and used as an collagen receptor antagonist for antiplatelet aggregation [ 108 ]. Salvianolic acid B (SB) is an active component isolated from Danshen ( Salvia miltiorrhiza ), a TCM widely used for the treatment of cardiovascular disorders.…”
Section: Antithrombotic Effects Of Natural Productsmentioning
confidence: 99%
“…GLA inhibited platelet aggregation induced by collagen-related peptide (CRP), a GPVI specific agonist in a dose-dependent manner and reduced collagen-induced phosphorylation of three major molecules, tyrosine kinase Syk, LAT, and phospholipase C γ 2 in GPVI signaling pathway. Therefore, GLA can be developed and used as an collagen receptor antagonist for antiplatelet aggregation [ 108 ]. Salvianolic acid B (SB) is an active component isolated from Danshen ( Salvia miltiorrhiza ), a TCM widely used for the treatment of cardiovascular disorders.…”
Section: Antithrombotic Effects Of Natural Productsmentioning
confidence: 99%
“…Glaucocalyxin A (GLA) [7a,14b-dihydroxy-ent-kaur-16-en-3,15-dione], a natural ent-kaurane diterpenoid with a molecular formula of C20H28O4, was isolated from Rabdosia japonica, as previously described [ 13 ]. Briefly, stems and leaves of Rabdosia japonica (Burm.…”
Section: Methodsmentioning
confidence: 99%
“…Initially isolated from this perennial herb in the early 1990s, a diterpenoid compound named glaucocalyxin A (GLA) was shown to have therapeutic effect in ischemic disease, leukemia, neurodegenerative disorders, and breast cancer [ 14 ]. We recently reported that GLA inhibits platelet activation and aggregation, with minimal bleeding risk [ 13 ]. Moreover, GLA was also shown to protect cardiomyocytes against oxidative stress and to ameliorate neuroinflammation [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Platelet membrane antigens were determined by flow cytometric analysis previously reported [21]. Washed platelets (5 × 10 7 cells/ ml) were preincubated with different concentrations of miltirone or vehicle for 5 min prior to activation with collagen (2.0 µg/ml) for 5 min at 37°C.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%